PFAS - Perfluorinated Organic Compounds In View Of The New Water Directive - Włodarczyk-Makuła, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of the work was to review the literature and characterize organic micropollutants from the group of perfluorinated surfactants - PFAS. It is a result of the proposal to include these compounds in the new Water Directive on the list of compounds which control in drinking water will be required and subject to inspection. The group of these organic bonds includes several thousand compounds in which fluorine is linked to the (straight or branched) chain of aliphatic hydrocarbons instead of hydrogen.
Keywords: perfluorinated compound (PFAS); water environment; water directive; związki perfluorowane; środowisko wodne; dyrektywa wodna